The freshmen reading program of St. Peter's College a survey and an evaluation, 1971-1974 - Lladoc, Letitia Morse 1941-
The author attempted to survey and evaluate the Freshmen Reading Program at St. Peter's College in Ormoc City during the school year 1971 through 1974. The study further involves an evaluation of the program by measuring its effects on the students' reading progress over a period of one year, in the areas of vocabulary comprehension and total reading ability.